'It’s all about you': the hopelessness of labels for young people and the workforce in secure and residential care - Rosie Urquhart-Stewart; Nicola Wylie (Scottish Journal of Residential Child Care)
Practitioners and policy makers have become increasingly aware of the importance of language used around children and young people within the care system. Existing research on young people and labels largely focuses on the impact of diagnostic labelling. More general explorations of how care experienced young people perceive labels calls for in-depth qualitative enquiry. This study aimed to elucidate how young people and the workforce experience labels in a secure and residential service using grounded theory and ethnographic methods. Researchers were full-time psychology staff within the host organisation with an already established nurturing relationship with participants which allowed for a rich view of their shared experience. The study finds that young people and the adults working to support them perceive that much of the everyday language they experience are labels which they often regard as negative and not conducive to empowerment. The findings provide insight into the issues within the Scottish care system and present an opportunity for improvement with the need for minimal resources.